Outlines of The Hittite Religion - (:unkn) unknown (CUMHURIYET UNIV, FAC THEOLOGY, 2016)
The Hittites who were origin of Indo-European and came to Anatolia occupied the region of Halys in central Anatolian around 1650 BC building Hattusa as a capital city. Expanding their territories into an empire they founded one of the most powerful states in their times and world. Including different ethnic groups Hittites called themselves by the expression of 1000 Gods of Hatti. Incorporating several local gods existed in the lands they conquered they have had a lot of gods or divines. Among these gods are gods of Hatti, Luwi, Pala, Sumer, Hurri, Assyro- Babilonian and ancient Indian. Many temples discovered in the Hattusa excavations are an important clue for their paying great respect to the gods. In this article benefiting from the evidences of archaeological and philological sources Hittite beliefs as a state religion and general aspects of this religion, gods in the pantheon, temples built for these gods, festivals devoted to these gods, the place of gods and humans, magic rituals, oracles, omens, prayers and mythological stories will be evaluated.
Keywords: Temple; God; Festival; Hittite; Hattusa